Modulation of Fatty Acids and Interleukin-6 in Glioma Cells by South American Tea Extracts and their Phenolic Compounds - Cittadini, María Cecilia (2018)
Dietary phenolic compounds are plant metabolites with beneficial effects on the central nervous system. Thus, our aim was to identify anti-inflammatory compounds from South American plants on glia, which regulates neuro-immune response. The compounds were extracted from Lantana grisebachii (LG), Aspidosperma quebracho-blanco (AQB), and Ilex paraguariensis (IP) teas and identified by HPLC-DAD-MS. Extracts (0–200 µg/ml) were tested on human T98-G and rat C6 glioma lines. Cellular viability (by the resazurin assay), fatty acid profile (by gas chromatography) and pro-inflammatory interleukin-6 release (IL-6 by ELISA) were determined. Data were analyzed by partial least-square regression to discriminate bioactive compounds. Twenty-one compounds were determined in LG, mainly iridoids, which were linked to ω-3 and ω-6 polyunsaturated fatty acids, but not to IL-6 release. Thirty-one compounds were found in AQB, mostly hydroxybenzoic derivatives, which were positively related to IL-6 release. Twenty-three compounds were identified in IP, including caffeoylquinic derivatives and mainly chlorogenic acid. They increased the ω-7 palmitoleic fatty acid, which was related to IL-6 decrease. These results enhances phytochemical knowledge of widely available plants, and suggest the lipid-related anti-inflammatory activity of IP phenolic compounds, which give nutritional relevance to the tea.